Cost‐minimization analysis of a tailored oral health intervention designed for immigrant older adults. Issue 2 (18th June 2013) - Mariño, Rodrigo J; Fajardo, Jorge; Calache, Hanny; Morgan, Mike
<x xml:space="preserve">Abstract</x> Aim This paper presents an economic evaluation, from a societal viewpoint, comparing a community‐based oral health promotion program aimed at improving the gingival health of immigrant older adults, with one‐on‐one chairside oral hygiene instructions at a public dental clinic in Melbourne, Australia. Methods The costs associated with implementing and operating the oral health promotion program were identified and measured using 2008 prices. The intervention was based on the Oral Health Information Seminars/Sheets model, and consisted of 10 20‐min oral hygiene group seminars and four 10‐min supervised individual brushing sessions carried out by a non‐oral health professional educator. Health outcomes were measured as a reduction in gingival bleeding. Clinical data showed a 75% reduction in mean gingival bleeding scores among those who took part in the intervention. A population of 100 active, independent‐living older adults living in Melbourne, and members of Italian social clubs, was used for modeling in this analysis. Results This analysis estimated that if an oral hygiene program using the Oral Health Information Seminars/Sheets model was available to 100 older adults, the net cost from a societal perspective would be AUD$6965.20. In comparison, a standard individual oral hygiene instruction program, at public dental clinics, given equivalent levels of case complexity and assuming the same level of effectiveness, would cost AUD$40 185.00. Per participant cost of a community‐based oral health promotion program was $69.65 versus $401.85 for chairside instruction. Conclusions Findings confirm that community‐based oral health interventions are highly cost‐effective and an efficient use of society's financial resources. Geriatr Gerontol Int 2013; 14: 336–340.